2014
DOI: 10.1007/s00586-014-3605-3
|View full text |Cite
|
Sign up to set email alerts
|

The severity of operative invasion to the posterior muscular-ligament complex influences cervical sagittal balance after open-door laminoplasty

Abstract: Open-door laminoplasty significantly affected postoperative cervical sagittal balance, with the cervical vertebra appearing to tilt forward. As the severity of surgical invasion to the posterior muscular-ligament complex increased, the loss of cervical sagittal balance also increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…16 Besides preoperative lordosis, loss of lordotic curvature is generally considered to be the result of posterior muscular-ligament complex disruption, especially the detachment of C2 extensor insertions during laminoplasty procedure. 13,17,18,26 In the present study, we found that plating at C3/C5 caused more LCL after laminoplasty when compared with those plated at C4/C6. Meanwhile, in the C3/C5 group, 94.1% of patients lost a certain degree of cervical lordosis and 23.5% of patients developed postoperative cervical kyphosis, both of which were significantly higher than the C4/C6 group.…”
Section: Discussionsupporting
confidence: 56%
“…16 Besides preoperative lordosis, loss of lordotic curvature is generally considered to be the result of posterior muscular-ligament complex disruption, especially the detachment of C2 extensor insertions during laminoplasty procedure. 13,17,18,26 In the present study, we found that plating at C3/C5 caused more LCL after laminoplasty when compared with those plated at C4/C6. Meanwhile, in the C3/C5 group, 94.1% of patients lost a certain degree of cervical lordosis and 23.5% of patients developed postoperative cervical kyphosis, both of which were significantly higher than the C4/C6 group.…”
Section: Discussionsupporting
confidence: 56%
“…Many modifications such as bone grafts, hydroxyapatite or other ceramic materials, allograft and titanium plates, titanium miniplates and screws have been developed to prevent this complication (2,7,20,21,39). We have preferred titanium miniplates (Blackstone Medical Inc, USA).…”
Section: █ Resultsmentioning
confidence: 99%
“…In patients with latent preoperative cervical sagittal imbalance, compensation is possible with excessive posterior muscle contraction to maintain a horizontal gaze. Therefore, damage to the posterior musculature resulting from laminoplasty may lead to decompensation, resulting in progression of cervical kyphosis [8].…”
Section: Discussionmentioning
confidence: 99%